Analysis of Factors For Increasing Income Tax in Motor Vehicles in UPT PPD (Technical Implementing Unit of Regional Revenue Management) in Siantar - Dona Hendrianto Damanik; Marlon Sihombing; Hamdani Harahap (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
In principle, motor vehicle tax plays a role in providing PAD for the North Sumatra Provincial Government. In this connection, the tax target must be increased every year and contribute to development in North Sumatra. To optimize the potential for motor vehicle tax revenue, it is necessary to know the factorsin increasing motor vehicle tax revenue at the UPT PPD (Technical Implementation Unit for Regional Revenue Management). ThereforeThe formulation of the problem in this study is as follows: "What factors influence itincrease in motor vehicle tax revenue at UPT PPD (Technical Implementation Unit for Regional Revenue Management) Pematang Siantar based onThe policy implementation approach is based on the formulation of the Van Meter and Van Horn models called A Model of the Policy Implementation. In this study the authors used a descriptive method with a research focus, namely the Analysis of Factors - Factors for Increasing Motor Vehicle Tax Revenues at UPT PPD (Technical Implementation Unit for Regional Income Management) Pematang Siantar ". The research site is an area whose location is used to obtain the data required for this research activity. The research results show thatMotor Vehicle Tax revenue factors, such as culture, communication, information, good cooperation with personnel and the use of renewable technology and so on, greatly affect the increase in Motor Vehicle Tax revenue at UPT Samsat Pematang Siantar.